IMPLEMENTASI PRINSIP KOLEKSI DINAMIS DI MUSEUM LINGGAM CAHAYA SEBAGAI SUMBER EDUKASI SEJARAH MELAYU - Nuragnianti, Mona Riza; Mahirta, Mahirta (Universitas Negeri Gorontalo, 2024)
Museum Linggam Cahaya plays an important role in improving the quality of Malay history learning in Lingga Regency. Improving museum services as a place of Malay history education must continue to be done for the community and tourists visiting Daik, Lingga Regency, Riau Archipelago. This research examines how to develop the storyline concept of museum collections as a Malay history education service. The research uses a case study method at the Linggam Cahaya Museum under the authority of the Lingga Regency Cultural Office, Riau Archipelago. Data collection using observation, and document analysis techniques. Observations were made by making direct visits, and through document analysis in the form of visitor data archives. The Baju Zirah kalimah collection is one of the dynamic Collection Implementations that help in shaping cultural identity and awareness, which can strengthen a sense of pride in Malay cultural heritage.